Contact assembly of cell-laden hollow microtubes through automated micromanipulator tip locating. (3rd November 2016) - Wang, Huaping; Shi, Qing; Guo, Yanan; Li, Yanan; Sun, Tao; Huang, Qiang; Fukuda, Toshio
Abstract: This paper presents an automated contact assembly method to fabricate a cell-laden microtube based on accurate locating of the micromanipulator tip. Essential for delivering nutrients in thick engineered tissues, a vessel-mimetic microtube can be precisely assembled through microrobotic contact biomanipulation. The biomanipulation is a technique to spatially order and immobilize cellular targets with high precision. However, due to image occlusion during contact, it is challenging to locate the micromanipulator tip for fully automated assembly. To achieve pixel-wise tracking and locating of the tip in contact, a particle filter algorithm integrated with a determined level set model is employed here. The model ensures precise convergence of the micromanipulator's contour during occlusion. With the converged active contour, the algorithm is able to pixel-wisely separate the micromanipulator from the low-contrast background and precisely locate the tip with error around 1 pixel (2 µ m at 4  ×  magnification). As a result, the cell-laden microtube is automatically assembled at six layers/min, which is effective enough to fabricate vessel-mimetic constructs for vascularization in tissue engineering.